2015
DOI: 10.1017/s0016672315000178
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of using next generation sequencing in newborn screening

Abstract: SummaryWhole-genome and whole-exome sequencing for clinical applications is now an integral part of medical genetics practice. The term newborn screening refers to public health programs designed to screen newborns for various treatable metabolic conditions, by measuring levels of circulating blood metabolites. The availability and significant decrease in sequencing costs has raised the question of whether metabolic newborn screening should be replaced by whole-genome or whole-exome sequencing. While newborn g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Here, we have demonstrated that it is technically feasible to perform targeted NGS on DBS DNA with a sufficiently high throughput and fast turnaround time that the assay could be used in a UK NBS pathway. To assess clinical sensitivity and specificity, the implementation of any targeted NGS assay for NBS should be carefully evaluated through pilot studies in the population to be screened [82,83]. This assessment was not an aim of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have demonstrated that it is technically feasible to perform targeted NGS on DBS DNA with a sufficiently high throughput and fast turnaround time that the assay could be used in a UK NBS pathway. To assess clinical sensitivity and specificity, the implementation of any targeted NGS assay for NBS should be carefully evaluated through pilot studies in the population to be screened [82,83]. This assessment was not an aim of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis contains features relating to the health of both the fetus and the parents [77]. Current methods including the combined test and invasive procedures (amniocentesis and chorionic villus sampling (CVS) used to screen the fetus for chromosomal abnormalities pose a risk to mother and fetus [78].…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…The widespread availability of whole-genome and whole-exon sequencing in clinical practice and the continuing significant decrease in cost of sequencing have raised the question of whether traditional metabolic newborn screening might be replaced by genome sequencing [ 9 ]. It has been clearly shown that DNA amplified from both old and new dried blood spots performs as well as their whole-blood reference samples with regard to error rates, indicating that DBSs are excellent sources of DNA for next-generation sequencing studies of disease [ 10 ].…”
mentioning
confidence: 99%